The Effects of Family Background on the Processes of Foreign Language Learning in Hungary - Fruzsina Szabo; Ágnes Albert; Kata Csizér (Debrecen University Press, 2021)
In Hungary, the academic achievement of schoolchildren is very strongly influenced by their family background, a statement often quoted in connection with PISA surveys (Róbert, 2004). Although the effects of family background have mostly been studied in connection with key competences, it is easy to see that they are also likely to influence foreign language learning, possibly to an even greater extent (Csapó, 2001). The aim of our paper is to provide an overview of theoretical and empirical findings related to the family background of Hungarian schoolchildren on different aspects of language learning: language choice, individual differences and success in language learning. We hope to provide a meta-analysis of empirical studies and their results, however it needs to be noted that their number is relatively scarce. We would also like to inspire future studies exploring similar, under-researched topics. Research into the effects of family background is imperative, as it appears to play a pivotal role in ensuring equal opportunities in language education.